Sabun Homemade Dengan Ekstrak Vitis Vinifera Menggunakan Framming Time - Roza Maiyarni; Hadi Purwanto; Annisa Miftahurrahmi; Suryanti (Postgraduate, University of Mataram, 2024)
Natural soap is one of the products that do not use chemicals that people need to clean the body and maintain healthy skin. Vitis vinifera and olive oil contain antioxidants and antimicrobials that are useful for brightening and moisturizing skin, increasing skin cell turnover, and making skin healthier. This research aims to obtain natural soap made from olive oil with the addition of grape extract (Vitis vinifera). The research method includes the process of making grape extract soap with varying framing times (3, 5, and 7 days), then the grape soap is stored for 4 weeks followed by analysis of pH levels, crack tests, and organoleptic tests including texture, color strength and foam. The final pH test results were in the range of 9.0-11.0 which were checked in the first seven days. This soap has texture ranges from 2.50 (slightly soft) to 3.84 (hard), soap color ranges from 3.15 (slightly interesting) to 4.00 (interesting), and foaming power ranges from 3.00 (slightly foamy) to 3.50 (foamy).